Brain Metabolite, N-Acetylaspartate Is a Potent Protein Aggregation Inhibitor - Warepam, Marina; Mishra, Awdhesh Kumar; Sharma, Gurumayum Suraj; Kumari, Kritika; Krishna, Snigdha; Khan, Mohd Sajjad Ahmad; Rahman, Hamidur; Singh, Laishram Rajendrakumar (Frontiers in Cellular Neuroscience, 2021)
Deposition of toxic protein inclusions is a common hallmark of many neurodegenerative disorders including Alzheimer’s disease, Parkinson disease etc. N-acetylaspartate (NAA) is an important brain metabolite whose levels got altered under various neurodegenerative conditions. Indeed, NAA has been a widely accepted biological marker for various neurological disorders. We have also reported that NAA is a protein stabilizer. In the present communication, we investigated the role of NAA in modulating the aggregation propensity on two model proteins (carbonic anhydrase and catalase). We discovered that NAA suppresses protein aggregation and could solubilise preformed aggregates.